2016
DOI: 10.1016/j.bios.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Diazonium-based impedimetric aptasensor for the rapid label-free detection of Salmonella typhimurium in food sample

Abstract: Fast and accurate detection of microorganisms is of key importance in clinical analysis and in food and water quality monitoring. Salmonella typhimurium is responsible for about a third of all cases of foodborne diseases and consequently, its fast detection is of great importance for ensuring the safety of foodstuffs. We report the development of a label-free impedimetric aptamer-based biosensor for S. typhimurium detection. The aptamer biosensor was fabricated by grafting a diazonium-supporting layer onto scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 62 publications
(64 reference statements)
1
63
0
2
Order By: Relevance
“…26 Aptamer 45 was chosen by Bagheryan et al to develop a label-free impedimetric aptamer-based biosensor for S. Typhimurium detection. 27 Han et al identified an RNase-resistant RNA aptamer I-2 specifically targeting outer-membrane protein C (OmpC) of S. Typhimurium. This selected aptamer specifically binds to S. Typhimurium but not to gram-positive bacteria ( S. aureus ) or to other gram-negative bacteria ( E. coli O157:H7).…”
Section: α-Toxinmentioning
confidence: 99%
“…26 Aptamer 45 was chosen by Bagheryan et al to develop a label-free impedimetric aptamer-based biosensor for S. Typhimurium detection. 27 Han et al identified an RNase-resistant RNA aptamer I-2 specifically targeting outer-membrane protein C (OmpC) of S. Typhimurium. This selected aptamer specifically binds to S. Typhimurium but not to gram-positive bacteria ( S. aureus ) or to other gram-negative bacteria ( E. coli O157:H7).…”
Section: α-Toxinmentioning
confidence: 99%
“…A label-free impedimetric aptamer-based biosensor for S. typhimurium was also fabricated by grafting a diazonium-supporting layer onto SPCEs followed by immobilization of an aminated-aptamer. This strategy allowed obtaining a dense aptamer layer, which resulted in a high sensitivity with a LOD of 8 cfu·mL −1 [123]. Also, a specific surface antigen, OmpD, was recently reported as a surface biomarker for detecting S. typhimurium.…”
Section: Electrochemical Affinity Biosensors For Microorganismsmentioning
confidence: 99%
“…), which is of key importance in food and water quality monitoring. Table 4 summarizes relevant information regarding recent reports on electrochemical affinity biosensors for microorganisms [118][119][120][121][122][123][124][125][126] and some important features of selected configurations are commented below.…”
Section: Electrochemical Affinity Biosensors For Microorganismsmentioning
confidence: 99%
“…Electrospun detection technique combined magnetic separation technique, capillary immunoassay, and direct electrical measurement for rapid and accurate sensing of the E. coli O157:H7 cells, the electrospun biosensor device has a linear detection for E. coli O157:H7 concentration of 10 1 to 10 4 CFU/mL with a low concentration of 67 CFU/mL . The impedimetric biosensor approach was implemented and studied (See Table ) by measuring the change in the impedance of the electrodes which indicates the presence or absence of the pathogen cells. These pathogen cells bind to the receptors such as antibodies that are immobilized on the interdigitated electrode arrays (IDEAs).…”
Section: Introductionmentioning
confidence: 99%